Strain tunable electronic properties of MoSi2N4/WSi2N4 heterostructure - Xuanhao Li; Jin Yu; Hongxia Zhong (AIP Advances)
Recently, a new family of layered two-dimensional materials, named MA2Z4 (M = Mo, W; A = Si; Z = N), have been attracting considerable attention due to their excellent ambient stability and physical properties. In this work, we systemically investigated the effect of mechanical strain on the electronic properties of the heterostructure of MoSi2N4/WSi2N4 by first-principles calculations. Our result shows that AC-stacked MoSi2N4/WSi2N4 is an indirect-gap semiconductor with a typical type-II band alignment. When vertical compression is applied, the heterostructure undergoes a transition from type-II to type-I to type-II band alignment accompanied by a decrease in the bandgap. Finally, the bandgap closes around a critical strain of −19%. We attribute this electronic phase transition to the enhanced polarization induced by the interfacial charge redistribution. It is also found that biaxially applied strain would induce a direct bandgap. Thus, the modulation of electronic properties proposed in the heterostructure holds great potential in electronic devices.